Pulsatile Conduit Pressure Gradients in the HeartWare HVAD. Issue 5 (July 2019) - Jain, Pankaj; Shehab, Sajad; Stevens, Michael; Macdonald, Peter; Jansz, Paul; Hayward, Christopher
Abstract : We evaluated mean, peak, and instantaneous pressure gradients across the outflow conduit in a pulsatile mock circulation loop which incorporated Heartware HVADs for left ventricular (LV) and right ventricular (RV) support. Steady-state 50 Hz measurements of left ventricular assist device (LVAD) flow (Q) and pressures within the proximal and distal outflow conduit were obtained at varying pump speed, LV contractility, hematocrit (HCT), heart rate (HR), and conduit diameter and length. Experiments were conducted using polyvinyl chloride (PVC) tubing and results confirmed in HVAD Gelweave conduit. Conduit diameter was negatively and nonlinearly associated with mean and peak gradient in both the PVC and HVAD conduits. There were no significant differences between the PVC and HVAD conduits in terms of mean Q, systolic dQ/dt, mean conduit gradient, or peak gradient. Across the 10 mm HVAD conduit, mean gradient correlated linearly with mean Q, systolic dQ/dt, HCT, and conduit length ( r 2 = 0.91), whereas peak gradient correlated with mean Q, systolic dQ/dt, and conduit length ( r 2 = 0.93). A nonlinear model to determine instantaneous gradient was highly predictive ( r 2 = 0.83) across a range of pump and circulatory conditions. In summary, hemodynamically significant pressure gradients are observed across the LVAD outflow conduit under physiologic conditions, which may result in diminished pump flow.